Correlates of fear of falling and falls efficacy in geriatric patients recovering from hip/pelvic fracture. (March 2020) - Eckert, Tobias; Kampe, Karin; Kohler, Michaela; Albrecht, Diana; Büchele, Gisela; Hauer, Klaus; Schäufele, Martina; Becker, Clemens; Pfeiffer, Klaus
Objective: To gain a better understanding about the nature of fear of falling, this study analyzed associations between psychological and physical aspects related to fear of falling and falls efficacy in hip/pelvic fracture patients. Design: Baseline data of a randomized controlled trial. Setting: Geriatric inpatient rehabilitation hospital. Subjects: In all, 115 geriatric patients with hip/pelvic fracture (mean age: 82.5 years) reporting fear of falling within first week of inpatient rehabilitation. Interventions: None. Main measures: Falls efficacy (Short Falls Efficacy Scale–International; Perceived Ability to Manage Falls), fear of falling (one-item question), fall-related post-traumatic stress symptoms (six items based on Diagnostic and Statistical Manual of Mental Disorders (4th ed.; DSM -IV) criteria), physical performance (Short Physical Performance Battery) and psychological inflexibility (Acceptance and Action Questionnaire-II) were assessed. Results: Path analyses demonstrated that low falls efficacy (Short Falls Efficacy Scale International) was significantly related to poor physical performance ( β * = –.277, P  ⩽ .001), but not to psychological inflexibility and fall-related post-traumatic stress symptoms ( P  ⩾ .05.). Fear of falling was directly associated with fall-related post-traumatic stress symptoms ( β *= .270, P  = .007) and indirectly with psychological inflexibility ( β *= .110, P  = .022). Low perceived ability to manage falls was significantly related to previous falls ( β * = –.348, P  ⩽ .001), psychological inflexibility ( β * = –.216, P  = .022) and female gender ( β * = –.239, P  ⩽ .01). Conclusion: Falls efficacy and fear of falling constitute distinct constructs. Falls efficacy measured with the Short Falls Efficacy Scale International reflects the appraisal of poor physical performance. Fear of falling measured by the single-item question constitutes a fall-specific psychological construct associated with psychological inflexibility and fall-related post-traumatic stress symptoms.